2022
DOI: 10.1002/dc.24945
|View full text |Cite
|
Sign up to set email alerts
|

Cytological and molecular characterization of secretory breast carcinoma

Abstract: Secretory breast carcinoma is a rare neoplasm, histologically well-characterized, and secondary to ETV6-NTRK3 gene fusion, whose cytological features are scarcely described in the literature. We report the case of a woman with a history of secretory breast carcinoma 8 years before, who presented a periareolar nodule.A recurrence was diagnosed by fine-needle aspiration based on the cytomorphological features and pan-TRK immunocytochemistry on the cell block, and the patient underwent a mastectomy. The histology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…It serves as a more cost-effective and rapid test than do ETV6 FISH or NGS-based assays. Similarly, Carretero-Barrio et al ( 62 ) also reported a case with recurrent SBC diagnosed by fine-needle aspiration based on the cytomorphological features and pan-TRK IHC on the cell block, and identified TRK overexpression, as a fusion surrogate, on the cytological sample. Furthermore, Remoué et al ( 56 ) found that only 1 of 339 invasive breast carcinomas was positive according to pan-TRK IHC staining and that other nonsecretory carcinomas do not harbor any TRK protein expression, showing negative for pan-TRK IHC.…”
Section: Histopathological and Genetic Characteristicsmentioning
confidence: 86%
“…It serves as a more cost-effective and rapid test than do ETV6 FISH or NGS-based assays. Similarly, Carretero-Barrio et al ( 62 ) also reported a case with recurrent SBC diagnosed by fine-needle aspiration based on the cytomorphological features and pan-TRK IHC on the cell block, and identified TRK overexpression, as a fusion surrogate, on the cytological sample. Furthermore, Remoué et al ( 56 ) found that only 1 of 339 invasive breast carcinomas was positive according to pan-TRK IHC staining and that other nonsecretory carcinomas do not harbor any TRK protein expression, showing negative for pan-TRK IHC.…”
Section: Histopathological and Genetic Characteristicsmentioning
confidence: 86%